Long term success of cavotricuspid isthmus ablation guided by the ablation index: results of the FLAI registry. (19th May 2022) - Viola, G; Stabile, G; Rossi, L; Figus, F; Gazzale, E; Casu, G; Bottoni, N; Deruvo, E; Scaglione, M; Santoro, A; Armenta-Pastor, J; Primo, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Cavotricuspid isthmus ablation (CTIA) is an effective treatment for typical atrial flutter (AFL) with a recurrence rate of about 10%. A prospective multicentric registry (FLAI registry) has recently shown that a protocol including 'point by point' CTI ablation targeting an a quality lesion marker (Ablation Index AI) ≥ 500 and a maximum inter-lesion distance (ILD) measurement of ≤6 mm allowed an acute success rate of 98.3%. In this study, we aimed to describe the incidence and predictors of recurrence of both AFL and atrial fibrillation (AF) in a long-term follow-up of the patients enrolled in the FLAI registry. Methods: The FLAI registry was a multicentric non-randomized study that enrolled 412 consecutive patients (mean age 64.9±9.8; 72.1% males; 27.7% with structural heart disease). Patients with typical AFL underwent an AI-guided cavotricuspid isthmus ablation. The procedures targeted an AI of 500 and an ILD measurement of ≤ 6mm. The primary endpoints were CTI 'first pass' block and persistent block after a 20-minute waiting period. The CTI bidirectional "first pass block" was reached in 355 patients (88.3%), whereas CTI block at the end of the waiting period was achieved in 405 patients (98.3%). No complications were reported. The mean time of follow-up was 21±4.24 months and it was available for 397 patients. The FU included outpatient clinical evaluation, ECG and 24-h Holter ECG at three, six- and 12-months post-ablation, followed by an annual clinical evaluation and ECG. Documented ECG Atrial fibrillation events, in follow up, were also included in the data set. Results: Atrial flutter recurrence: 22 AFL events were observed (5.5%) at 34 months. According to the Kaplan Meier analysis, the growth of recurrence rate was constant between 6 and 12 months, after 19 months recurrences were unlikely. At the univariate analysis predictors of AFL recurrence were: absence of bidirectional block after the waiting time period (p= 0, 001); failure of the CTIA index procedure (p=<0, 0005); ablation line lengths > 32 mm (p=0., 018), number of automatic ablation lesion tags (VISITAG) > 20 (p=0, .005) and At the increathe reported numbers of 'g"gap'" in the ablation line lengths: the more the gaps increase the more the probability of AFL recurrence in FU increases (p=0., 037). In the Multivariate aAnalysis, the independent predictors of AFL recurrence were: the procedural success and the number of VISITAG (OR =1.062) Atrial fibrillation recurrence: 45 patients developed atrial fibrillation after CTI ablation (11.3%). In the multivariate analysis, the major independent predictor was a documented pre-procedural Afib and the risk increases with the younger age (< 53 yo). Conclusions: The FLAI protocol is safe, reproducible and effective in the follow-up, with a long term success of 94, 5%. The reported incidence of atrial fibrillation in FU was 11, 3%